2013
DOI: 10.1248/cpb.c13-00490
|View full text |Cite
|
Sign up to set email alerts
|

Steroidal Constituents from the Starfish <i>Astropecten polyacanthus</i> and Their Anticancer Effects

Abstract: Using various chromatographic methods, four new steroids, astropectenols A-D (1-4), along with three known compounds (5-7) were isolated from a methanol extract of the starfish Astropecten polyacanthus. The structure elucidation was confirmed by spectroscopic methods, including one dimensional (1D)-, 2D-NMR and Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS). The CH 2 Cl 2 fraction and compound 7 exhibit potent cytotoxic effects against HL-60 human leukemia cells with the IC 50 of 8.29 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 11 publications
0
14
0
2
Order By: Relevance
“…Astropecten species are abundant in the Vietnamese sea, and have been used as tonic agents in Vietnamese folk medicine. In previous studies, we isolated and identified seven steroids ( 1 – 7 ) from A. polyacanthus (Figure 1), some of which had cytotoxic effects against HL-60 (leukemia), PC-3 (prostate), and SNU-C5 (colorectal) human cancer cells [17]. In continuation of our investigations on Vietnamese marine organisms regarding anti-inflammatory activity [18,19,20,21], we found that the MeOH extract and CH 2 Cl 2 partition showed significant in vitro anti-inflammatory activities.…”
Section: Introductionmentioning
confidence: 99%
“…Astropecten species are abundant in the Vietnamese sea, and have been used as tonic agents in Vietnamese folk medicine. In previous studies, we isolated and identified seven steroids ( 1 – 7 ) from A. polyacanthus (Figure 1), some of which had cytotoxic effects against HL-60 (leukemia), PC-3 (prostate), and SNU-C5 (colorectal) human cancer cells [17]. In continuation of our investigations on Vietnamese marine organisms regarding anti-inflammatory activity [18,19,20,21], we found that the MeOH extract and CH 2 Cl 2 partition showed significant in vitro anti-inflammatory activities.…”
Section: Introductionmentioning
confidence: 99%
“…To date, no investigations of their biological activities have been reported. In the course of our search for new biologically active compounds from Vietnamese starfish, [8][9][10] six asterosaponins, astrosteriosides A-D (1-3 and 5), psilasteroside (4), and marthasteroside B (6), were recently isolated from the starfish A. monacanthus ( Fig. 1) and their anti-inflammatory effects were evaluated.…”
mentioning
confidence: 99%
“…The steroids exhibited moderate cytotoxicity and inhibitory activity against phospholipase A2. [58] Rare steroid, cytotoxic astropectenol C (46) with 8,9-epoxy group was obtained from a methanol extract of the starfish Astropecten polyacanthus, [59] and (3,5,7,8,14,24R)-7,8-Epoxy-14-methoxy-4-methyleneergostan-3-ol (47) was obtained from sponge Theonella swinhoei. [60] The cytotoxic polyoxygenated sterols, homaxisterols B1 (48) and B2 (49) have been isolated from the MeOH extract of the marine sponge Homaxinella sp.…”
Section: Steroids Bearing 56-epoxy Groupmentioning
confidence: 99%